Koszty świadczenia pozaprodukcyjnych funkcji gospodarki leśnej na przykładzie Regionalnej Dyrekcji Lasów Państwowych w Katowicach - Gołos, Piotr (Leśne Prace Badawcze, 2012)
The aim of this study was to determine the total costs of selected public forest management functions incurred in the years 2005–2009 by the Forest Districts of the Regional Directorate of State Forests (RDLP) in Katowice. The analysis covers: 1) direct costs related to non-productive functions of forest management, 2) alternative/opportunity costs, also known as the cost of lost opportunities, including: – the increased cost of timber production due to limitations in the choice of forest operational practices (management, conservation and forest utilization), – reduced revenues from timber sales as a result of leaving standing and cut trees in the forest (dead wood). This research was carried out using data costs from the State Forest IT System, comparing groups of activities. The sum total of costs incurred amounted to over 73 million PLN (excluding the value of wood left in the forest). For the public sector coverage, forest management is allocated 120 PLN ha -1 and 24 PLN year -1 ha -1 , and 4.53 PLN m -3 of timber. Additionally, as a consequence of leaving dead wood in the forest, the Forest Districts lost income of 326 million PLN, i.e. 536 PLN ha -1 .